Кто и за какую интеграцию? (Отношение населения стран ЕС и СНГ к интеграции) - Фурман, Екатерина (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
Integration processes in the European Union and in the Commonwealth of Independent States (CIS) are an element of a global tendency to form suprastate associations. Although such associations assume that supranational systems of authorities are created they are hardly antidemocratic. Nevertheless, each such integration process, although formally identical or highly similar, may have a completely different political or social significance which can be observed when their social support is compared. The European Union is practically unprecedented, and such a model of integration is being created for the first time in response to the requirements and needs of modern European society; it also has no determined borders. It mainly finds support among the young and educated social strata, who are interested in the benefits generated by such integration and who do not fear potential instability and indeterminacy that accompany such processes. The Post-Soviet countries do have recent experience of integration having followed a model of a state with a highly integrated social and political life. The experience of the Soviet Union in many respects determines the directions of integration of these states although the USSR collapsed and the historic circumstances that affected its foundation are radically different. The nature of such integration efforts is reflected by their social support. The main advocates of the integration processes in CIS are older and less educated people for whom the revival of Soviet reality seems more attractive whereas the present brings risk and threat. Thus being oriented to the past or to the future is among the main factors that differentiate the nature, efficiency and future prospects of these two integration processes.